T Follicular Helper Cells and Regulatory B Cells Dynamics in Systemic Lupus Erythematosus - Yang, Xue; Yang, Ji; Chu, Yiwei; Xue, Yu; Xuan, Dandan; Zheng, Shucong; Zou, Hejian (PLOS ONE, 2014)
T follicular helper (Tfh) cells aid effector B cells, and augment autoimmunity, whereas the role of Tfh cells on regulatory B (Breg) cells in systemic lupus erythematosus (SLE) is not known. The aim of this study is to investigate the percentage of Breg cells in SLE, and the role of Tfh cells on Breg cells. First, we demonstrated the presence of Breg cells in SLE peripheral blood mononuclear cells and in involved skins. Both the percentage of circulating Breg cells and the ability to produce interleukin-10 (IL-10) were elevated in SLE patients. The percentage of Breg cells increased during SLE flares and decreased following disease remission. Second, Tfh cell expansion was not only related to autoantibody production but also correlated with the increased percentage of Breg cells. Third, in vitro studies revealed that Tfh cell-derived IL-21 could promote IL-10 production and Breg cell differentiation. In conclusions, these data imply that SLE flares may be linked to the expansion of Tfh cells and that Breg cells are increased in a regulatory feedback manner. Thus, SLE development may be associated with the complex regulation of Tfh cells and diverse B cell subsets.